Advances in materials used for minimally invasive treatment of vertebral compression fractures - Sui, Pengfei; Yu, Tong; Sun, Shouye; Chao, Bo; Qin, Cheng; Wang, Jingwei; Wang, Erwei; Zheng, Changjun (Frontiers in Bioengineering and Biotechnology, 2023)
Vertebral compression fractures are becoming increasingly common with aging of the population; minimally invasive materials play an essential role in treating these fractures. However, the unacceptable processing-performance relationships of materials and their poor osteoinductive performance have limited their clinical application. In this review, we describe the advances in materials used for minimally invasive treatment of vertebral compression fractures and enumerate the types of bone cement commonly used in current practice. We also discuss the limitations of the materials themselves, and summarize the approaches for improving the characteristics of bone cement. Finally, we review the types and clinical efficacy of new vertebral implants. This review may provide valuable insights into newer strategies and methods for future research; it may also improve understanding on the application of minimally invasive materials for the treatment of vertebral compression fractures.